Solve f(x)=(x − 3)(x − 1)(x + 1) = 0 by using intersection with the coordinate axes.

### 1 Answer | Add Yours

The solution of f(x) = (x - 3)(x - 1)(x + 1) = 0 is all the points that lie on the x-axis and have a y-coordinate equal to 0.

(x - 3)(x - 1)(x + 1) = 0

when (x - 3) = 0 or (x - 1) = or (x + 1) = 0

=> x = 3 or x = 1 or x = -1

**The solution of the equation (x - 3)(x - 1)(x + 1) = 0 is {-1, 1, 3}**

### Join to answer this question

Join a community of thousands of dedicated teachers and students.

Join eNotes